Identity, Multiculturalism and the Democratic Imperative in Ahmed Yerima's the Silent Gods: A Critical Discourse - Adeoti, G. R. (2014)
One major factor that has hindered the growth of democracy in many post-independent African countries is the invidious manipulation of identities, especially by the elites, in the competition for limited national resources. Identities may be ethno-geographical, sexual, religious or generational in nature. It becomes difficult to secure a consensus on issues of democratisation among the people and in combating autocratic tendencies of postcolonial leaders, whether military or civilian. It breeds electoral fraud, nepotism, thuggery and arson. The consequence is that democratic governance is imperiled in such a dispensation.